2023
DOI: 10.1007/s00380-023-02251-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between complete revascularization of the coronary artery and clinical outcomes in peripheral artery disease: a sub-analysis of the I-PAD Nagano registry

Abstract: Peripheral artery disease (PAD) is commonly caused by atherosclerosis and has an unfavorable prognosis. Complete revascularization (CR) of the coronary artery reduces the risk of major adverse cardiovascular event (MACE) in patients with coronary artery disease (CAD). However, the impact of CR in patients with PAD has not been established to date. Therefore, we evaluated the impact of CR of CAD on the five-year clinical outcomes in patients with PAD. This study was based on a prospective, multicenter, observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…In addition, patients with combined CAD and LEAD have a high risk of cardiovascular death [ 15 ]. It has also been reported that in patients with combined CAD and LEAD, clinical outcomes were significantly better with complete CAD revascularization than with incomplete CAD revascularization [ 16 ]. Moreover, compared to patients with CAD, the control of cardiovascular risk factors is poor in patients with LEAD [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients with combined CAD and LEAD have a high risk of cardiovascular death [ 15 ]. It has also been reported that in patients with combined CAD and LEAD, clinical outcomes were significantly better with complete CAD revascularization than with incomplete CAD revascularization [ 16 ]. Moreover, compared to patients with CAD, the control of cardiovascular risk factors is poor in patients with LEAD [ 17 ].…”
Section: Discussionmentioning
confidence: 99%